Juice Paradise / Nurkhairunnisa Mohd Salleh ... [et al.] - Mohd Salleh, Nurkhairunnisa; Ramlan, Mohammad Raimi; Petrus, Fennie; Alias, Saida; Mohd Arif, Sarina (2011)
This business plan is Juice Paradise, a new small-sized cafeteria located at One Borneo Hypermall which leisure places, Kota Kinabalu. Juice Paradise emphasis will be on healthy juice drinks. The market can be segmented into three different groups that it aims to target. The groups are women, men and children. This type of groups will go thru our cafeteria during go and return from Office and also during weekend for leisure purpose. Juice Paradise has assembled a strong management team. Firstly, Nur Khairunnisa Mohd Salleh will be the General Manager also reacts as an office leader to ensure all the restaurant activity will work effectively; Saida Alias will be responsible for all the operation process from raw material to customer or end user. Next, Sarina Mohd Arif will be responsible for all of the finance and accounting functions which will be invaluable in keeping Juice Paradise on track and profitable. Marketing Manager is Fennie Petrus which will be arranging the entire marketing project to introduce our cafeteria to the public which including planning all the marketing strategy. Last but not least, the Administration Manager, Mohammad Raimi Ramlan responsible to control all the activity outside and will act as a public relation to deal with the supplier. Our business will be set as a partnership business. We all agree to undertake a joint business and jointly own the business and will carry out the business, share the capital, and profits. Our contribution is RM 18000 and some contribution of assets such as laptop, blender, freezer and refrigerator. Other resources of capital will be from the bank. We will take loan as RM 15,000.